The General Theory of Location and Space-Economy - Isard, Walter (Quarterly Journal of Economics, 1949)
I. Introduction, 476. — II. Early contributions to general location theory: the evolutionary approach of Alfred Weber, 479. — III. Predöhl and the substitution principle in location analysis, 482. — IV. The contribution of Hans Weigmann, 489. — V. The Lösch model of a space-economy operating under conditions of monopolistic competition, 494. — VI. The inter relation of trade and location theories, 502. — VII. Conclusion, 505.